(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2021)
The objective of this text is to offer an introduction to the conceptualization of evil within the religious beliefs and to bring closer to the Macedonian public the basic definitions regarding the concept of evil incarnate, through the beliefs in demons in Ancient Egypt. Therefore, some fundamental terminological distinctions are briefly mentioned, concerning the use of demon and daimon in ancient contexts, as well as the basic conceptual framework of the demonic, the hybrid, the monstrous. A basic comparison is made between the nature of demons in the Eastern civilizations and the daimons of the Greek intellectual culture, and some light is shed on the differences between the ancient and the Christian (and modern) understanding of evil incarnate, as well as on the monstrosity or the “existence between” of creatures with an uncertain ontological status and a potentially menacing nature. Some attention is paid to these “creatures between”, believed to move between the different realities (the earth and the underworld, the world of the living and of the dead, the profane and the sacred), which should not be determined as strictly, or purely, evil and harmful. The text examines the types of demons from the aspect of their nefariousness or usefulness, as well as from the aspect of their topography (wanderers vs. fixed ones); the ways in which the harmful (mobile) demons proliferate diseases and attack the souls and bodies of the human patients, as well as the importance of the magico-medial protection against such influences; and the ways in which the useful guardian-demons (fixed in certain places, on earth or the Netherworld), participate in preserving the safety оf the chosen areas they protect. Some attention is given, thus, to the importance which both categories of demons have in understanding the functioning of the Netherworld. The ancient beliefs in the demonic, besides it being seen as threatening, dangerous, and nefarious, include a certain ambivalence of the concepts: the harmful demons, disease-bringers, bringers of problems and troubles, sometimes act according to the orders by the gods, or serve to punish the sinful in the Netherworld. The useful demons have key ontological roles in keeping the balance between the worlds, by serving as keepers and guardians of the gates to the Netherworld, the entrances to the sacred places, the sacred realms, and the liminal spheres. Thus, an attempt is made with this text to underline the need for a broad approach in the understanding of the concept of the demonic.